Finding the 'boundary mediators': network analysis of the joint R&D project between Toyota and Panasonic. (1st January 2014) - Tsujimoto, Masaharu; Matsumoto, Yoichi; Sakakibara, Kiyonori
In recent years, a large and growing number of companies have attempted to develop core technologies for their products by conducting joint research with a company in a different industry. However, the mechanisms by which technologies are acquired and assimilated through cross-industry research remains unclear. In response to this ambiguity, we developed a theoretical framework for this mechanism, proposed hypotheses, and empirically examined data from a joint research project conducted by Toyota Motor Corporation and Panasonic Corporation to develop the nickel-hydrogen storage cell. Specifically, we analysed networks of inventors who filed patent applications through the joint research. The results indicate that there are 'boundary mediators' who facilitated the exchange of technologies between the two companies. On the basis of their wide range of technical knowledge, we found there to be two types of boundary mediators.